Using chromosome engineering on a natural isolate of the fission yeast, Schizosaccharomyces pombe, to investigate the epigenetic inheritance of the kinetochore - Barbosa, Anne Caroline (2018)
In many eukaryotes, kinetochores may form over a variety of unrelated centromeric sequences. This fact has led to the idea that an epigenetic process determines kinetochore location. To investigate the nature of this epigenetic process, I have established a system that allows the manipulation of the chromosomal centromeric DNA in a genetically tractable model organism, Schizosaccharomyces pombe. The system enables the definition of the relationship between centromeric DNA size, sequence, chromosome position and function. I have used this system to measure how binding of the conserved kinetochore protein Cnp1 (CENP-A homolog) varies as a function of the amount, sequence and position of the centromeric DNA. In humans, cytogenetic data suggests that the number of centromere-specific CENP-A nucleosomes at each centromere is approximately uniform regardless of the sequence and length of the centromeric DNA. These observations suggest that the number of these centromere-specific nucleosomes is tightly regulated. I set out to test whether such mechanism is evolutionarily conserved in the fission yeast S. pombe. I did this by manipulating the amount of the centromeric DNA at one centromere and then measuring the amount of Cnp1 bound to it. The results showed that in S. pombe, the amount of bound Cnp1 is proportional to the amount of centromeric DNA and thus the relationship between centromeric DNA size and CENP-A binding differs from humans. During these measurements, I observed that the size and sequence of the centromeric DNA do have a role in determining Cnp1 binding to centromeric DNA but, as described by others, it is not sufficient and sometimes not necessary for functional centromere formation. The requirement of the kinetochore protein Swi6 for neo-centromere formation but not for the maintenance of a pre-established centromere was also confirmed.